Pengaruh Kualitas Pelayanan dan Kepercayaan Terhadap Kepuasan dan Loyalitas Konsumen di OMI Market Karya Nuklida Yogyakarta - Budi Astuti; Abkhoro Fasta Wantono (Jurnal Aplikasi Bisnis, 2017)
This study entitled "The Effect of Service Quality and Satisfaction Confidence Against Consumer Loyalty". The purpose of this study was to clarify whether service quality has a effect on customer satisfaction, explain whether service quality has a effect on consumer loyalty, explain whether customer satisfaction has a influence on consumer loyalty, explain whether consumer confidence has a effect or customer satisfaction and to clarify whether consumer confidence has a effect on consumer loyalty. Data used in this study is the type of quantitative data , while the methods for collecting data to measure variables is to use a questionnaire with the help of a computer program SPSS for Windows Evaluation version 17:00 and the results of data analysis using SEM. The results of the analysis of the Structural Equation Model (SEM) showed that the variables of service quality has a significant influence on customer satisfaction and customer loyalty, customer satisfaction variables have a significant influence on consumer loyalty and consumer confidence variables have a significant influence on customer and customer loyalty.